Jamaica Debt Exchange - Grigorian, David (IMF Working Papers; Working Paper ;, 2012)
The sovereign debt restructuring operation in Jamaica undertaken in early-2010 was a unique experiment that perhaps offered less by way of upside, if compared to the conventional sovereign debt exchanges, but provided credible assurances against further downfall and financial sector distress. A case study of a highly indebted country with domestically held debt, the paper discusses the conditions leading to the exchange, the rationale behind it, as well as its operational aspects. Achievements of the exchange, too, are discussed in detail. The paper also outlines the risks stemming from the high levels of debt-which continue to remain high-requiring prompt and coordinated action by policymakers if the legacy of the debt exchange is to be preserved.